DOSES AND PERIODS OF BORON FOLIAR APPLICATIONS ON AGRONOMIC CHARACTERISTICS AND QUALITY OF SOYBEAN SEEDS - KAPPES, Claudinei; GOLO, André Luis; CARVALHO, Marco Antônio Camillo de (Scientia Agraria, 2008)
The boron is an essential nutrient for the soybean crop, however, the management of its fertilizer should be wary. Thus, to evaluate the effect of foliar fertilization of boron on the agronomic characteristics and quality of soybeans seed we carried out experiments at Santa Carmem, Mato Grosso State, Brazil, in the 2005/06 agricultural year. The experiment design was randomized blocks in factorial arrangement 3 x 5 (periods x doses), with 4 replicates. The periods of application were in V5, V9 and R3 fase and doses of 0, 100, 200, 300 and 400 g ha-1 of the boron. Evaluations were carried out in the morphological characteristics, production components and tests of the physiological quality seeds. The results were submitted to the analysis of variance, and the times compared by Tukey test and the doses for polynomial regression. The plant height was influenced by the dose of boron, and observed interaction between the factors tested, noting that the times had different behavior in their averages for a dose of 200 g ha-1 B. There was isolated end of the period on the number of pods per plant, and the application in the showed the best result V5 fase. Productivity and quality physiological seeds were not affected by the application of boron, however, they did not attain the necessary marketing potential.